Culture, Subjectivity and the Ethics of Patient-Centered Pain Care: Културата, субјективноста и етиката на пациентоцентричната нега на болката - Giordano, James; Engebretson, Joan C.; Benedikter, Roland; Ruskovska, Rodna (Identities: Journal for Politics, Gender and Culture, 2008)
Author(s): James Giordano, Joan C. Engebretson and Roland Benedikter | Џејмс Џордано, Џоан С. Енгебретсон и Роланд Бенедиктер Title (English): Culture, Subjectivity and the Ethics of Patient-Centered Pain Care Title (Macedonian): Културата, субјективноста и етиката на пациентоцентричната нега на болката Translated by (English to Macedonian): Rodna Ruskovska | Родна Русковска Journal Reference: Identities: Journal for Politics, Gender and Culture, Vol. 7, No. 1-2 (Summer 2008 - Winter 2009) Publisher: Research Center in Gender Studies - Skopje and Euro-Balkan Institute Page Range: 9-32 Page Count: 23 Citation (English): James Giordano, Joan C. Engebretson and Roland Benedikter, “Culture, Subjectivity and the Ethics of Patient-Centered Pain Care,” Identities: Journal for Politics, Gender and Culture, Vol. 7, No. 1-2 (Summer 2008 - Winter 2009): 9-32. Citation (Macedonian): Џејмс Џордано, Џоан С. Енгебретсон и Роланд Бенедиктер, „Културата, субјективноста и етиката на пациентоцентричната нега на болката“, превод од англиски Родна Русковска, Идентитети: списание за политика, род и култура, т. 7, бр. 1-2 (лето 2008 - зима 2009): 9-32.